2019
DOI: 10.1111/ecc.13064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of home‐based music intervention versus ambient music on breast cancer survivors in the community: A feasibility study in Taiwan

Abstract: To explore the effects of home‐based music intervention (HBMI) on symptom severity, pain intensity and perceived fatigue among patients with breast cancer. In this randomised controlled trial, patients with breast cancer were randomly assigned into an HBMI or control group. The HBMI group was administered 24‐week HBMI involving five 30‐min sessions per week. The primary outcome was symptom severity; the secondary outcomes were pain and fatigue. A generalised estimating equation was employed to compare the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 42 publications
2
19
1
4
Order By: Relevance
“…ese findings are consistent with another RCT indicating pain reduction effect of music therapy after surgery [39]. Recent study showed that even home-based music therapy may have lasting effect (up to 24 weeks) not only on pain intensity, but also on overall and general fatigue, emotional fatigue, and vigor [46]. Besides anxiety or depression evaluation, two studies also measured the effect of music therapy on nausea and vomiting [45] and sedative requirements [43], but could not confirm associations between them.…”
Section: Music Erapysupporting
confidence: 89%
“…ese findings are consistent with another RCT indicating pain reduction effect of music therapy after surgery [39]. Recent study showed that even home-based music therapy may have lasting effect (up to 24 weeks) not only on pain intensity, but also on overall and general fatigue, emotional fatigue, and vigor [46]. Besides anxiety or depression evaluation, two studies also measured the effect of music therapy on nausea and vomiting [45] and sedative requirements [43], but could not confirm associations between them.…”
Section: Music Erapysupporting
confidence: 89%
“…Com relação à musicoterapia, o estudo 31 constatou que esta é uma estratégia eficaz na redução da fadiga, após realizar sessões individuais de 30 a 40 minutos com músicas clássicas, românticas e barrocas escolhidas pela pesquisadora, sendo realizada duas vezes por semana antes das sessões de radioterapia. Um estudo desenvolvido em Taiwan também mostrou eficácia da música sobre a dor e fadiga, após realizar cinco sessões de 30 minutos, cinco vezes na semana, com músicas clássicas, típicas de Taiwan, religiosas e de salão 49 .…”
Section: Categoria 2 Terapias Integrativas E Complementaresunclassified
“…However, these results should be interpreted with caution. No harassment assessment [43,44] was performed in this trial as the trial was initially not designed to collect the measures regarding bullying of participants. Only the data collected from the primary study has been discussed [13].…”
Section: Limitationsmentioning
confidence: 99%
“…Stress related psychiatric conditions including mood and substance use are associated with suicidal thinking and behavior [42], post-traumatic stress disorder (PTSD) and increased incidence of domestic violence [43]. A multicenter, cross-sectional survey of 4,692 nurses in China working during the COVID-19 pandemic found that 9.4% had symptoms of depression, 8.1% had anxiety and 6.5% had suicidal thinking [44]. A second study of 8817 HCWs in China uncovered prevalence of depression (30%), anxiety (21%), and suicidal thinking (6.5%) due to psychological stress during the pandemic [45].…”
Section: Psychological Effects Of the Pandemicmentioning
confidence: 99%